2018
DOI: 10.1021/acs.jproteome.7b00770
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomic Analysis of Exosomes and Microvesicles in Human Saliva for Lung Cancer

Abstract: Extracellular vesicles (EVs) are cell-derived microparticles present in most body fluids, mainly including microvesicles and exosomes. EV-harbored proteins have emerged as novel biomarkers for the diagnosis and prediction of different cancers. We successfully isolated microvesicles and exosomes from human saliva, which were further characterized comprehensively. Salivary EV protein profiling in normal subjects and lung cancer patients was systematically compared through utilizing LC-MS/MS-based label-free quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(101 citation statements)
references
References 22 publications
2
98
0
1
Order By: Relevance
“…As carriers of disease‐associated molecules that can be found in biofluids, EVs have great potential as a noninvasive source of biomarkers for diseases such as cancer. Recently three groups (Hwang, Buzás, and Xiao) have performed comparative proteomic analysis on EVs from disease‐associated biofluids . Proteomic analysis of EVs from biofluids has been shown to decrease the background signal derived from highly abundant proteins, such as creatine in urine, resulting in greater sensitivity .…”
Section: Proteomic Profiling Of Evs In Clinical Samplesmentioning
confidence: 72%
See 1 more Smart Citation
“…As carriers of disease‐associated molecules that can be found in biofluids, EVs have great potential as a noninvasive source of biomarkers for diseases such as cancer. Recently three groups (Hwang, Buzás, and Xiao) have performed comparative proteomic analysis on EVs from disease‐associated biofluids . Proteomic analysis of EVs from biofluids has been shown to decrease the background signal derived from highly abundant proteins, such as creatine in urine, resulting in greater sensitivity .…”
Section: Proteomic Profiling Of Evs In Clinical Samplesmentioning
confidence: 72%
“…Similarly, the study from Xiao lab showed that BPIFA1 and CRNN were significantly enriched in l‐EVs, while MUC5B and IQGAP were enriched in s‐EVs from the saliva of lung cancer patients compared to healthy donors. Importantly, these differences were not observed when saliva was analyzed without EV isolation …”
Section: Proteomic Profiling Of Evs In Clinical Samplesmentioning
confidence: 96%
“…They determined that a starch‐packed affinity chromatography column combined with filtration was the optimal method to deplete saliva of amylase and enrich for EV proteins. Using this methodology, they explored the proteome of EVs from NSCLC patients as well as healthy subjects using LC–MS/MS‐based label‐free quantification . In their first report, both serum and saliva were analyzed from three healthy controls and three lung cancer patients.…”
Section: Salivamentioning
confidence: 99%
“…Exosomes are rich in biomolecules that reflect the state and the composition of progenitor cells; they are a rich source of biomarkers [383]. In fact, genomics [388], transcriptomics [388], proteomics [389], and metabolomics [390] analyses can be applied to exosome-derived biomarkers. Importantly, because exosomes can be readily isolated from blood, plasma, saliva, urine, breast milk, semen, ascites fluid, amniotic fluid, and cerebrospinal fluid, they are an ideal target for liquid biopsy.…”
Section: Scientific Rationalementioning
confidence: 99%
“…Exosome proteomes can be probed for biomarkers in an unbiased way, using untargeted MS-proteomics approaches [413,414], or using affinity-based approaches, such as binding to aptamer-based SOMAscan arrays [415]. Indeed, studies have shown that single protein biomarkers and protein panels from exosomes have the potential to be used as diagnostic and prognostic biomarkers in pancreatic cancer [416,417], melanoma [418], lung cancer [389], and colorectal cancer [419].…”
Section: Current and Emerging Technologies And Biomarkersmentioning
confidence: 99%